Economic loss in Czech photovoltaic power plants - Jan Průša; Andrea Klimešová; Karel Janda (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This text provides a financial survey of a small sample of Czech photovoltaic (PV) plants. To evaluate the extent of market losses, we calculate the shadow market price of solar electricity. From the profit and loss accounts of the PV plants and the shadow market price we estimate the total economic loss generated by PV electricity sector in the Czech Republic. The presented microeconomic approach has two main advantages: Firstly, we work with real observed data, which offsets the drawback of a limited sample. Secondly, the profit accounting calculation enables sensitivity analysis with respect to key variables of the plants. We show that every million invested in PV plants would generate an annual loss of 11%. Given the estimated solar assets of CZK 127.4 billion (EUR 560 million) as of December 2010, this translates in at least CZK 14 billion lost in the Czech solar sector in 2011. About 42% of this loss is due to high technology costs and corresponds to pure dead weight loss, while the remaining 58% constitute the redistributive profit component of subsidies. Finally, we calculate that unless electricity prices increase or technology costs decrease approximately tenfold, PV plants will remain loss making.
Keywords: Q42; H23; M21; 330; energy subsidies; photovoltaic; renewables